1981
DOI: 10.1093/oxfordjournals.aje.a113126
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (Hbv) Infection Among Children and Adults in the Solomon Islands

Abstract: A total of 593 inhabitants of Graciosa Bay, Santa Cruz, the Solomon Islands were tested for HBsAg and anti-HBs in 1974 and again in 1977. An additional 102 children born during this study period were tested for HBsAg and anti-HBs in 1977. Loss of HBsAg was observed in 20% of the 66 HBsAg-positive individuals identified in 1974 and retested in 1977. Conversely, acquisition of HBV infection, as documented by seroconversion on HBsAg or anti-HBs, was observed in 38% of the individuals identified as negative for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…12 Our laboratory previously reported that the prevalence of HBV infection has remarkably decreased in children and young adults in Okinawa, a subtropical area in Japan that was endemic for HBV from 1970 to 1996 because of both the impact of vaccination and improvements in sanitary conditions, and suggested that HBV infection will be eliminated there in the near future. 31,34 It was reported in the Solomon Islands that the high prevalence of HBsAg determined by RIA was 11.2-13.0% in the 1970s, 33,35 a finding similar to our recent results. Because the sanitary conditions have not improved greatly in this area for two decades, the prevalence of HBsAg has not changed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…12 Our laboratory previously reported that the prevalence of HBV infection has remarkably decreased in children and young adults in Okinawa, a subtropical area in Japan that was endemic for HBV from 1970 to 1996 because of both the impact of vaccination and improvements in sanitary conditions, and suggested that HBV infection will be eliminated there in the near future. 31,34 It was reported in the Solomon Islands that the high prevalence of HBsAg determined by RIA was 11.2-13.0% in the 1970s, 33,35 a finding similar to our recent results. Because the sanitary conditions have not improved greatly in this area for two decades, the prevalence of HBsAg has not changed.…”
Section: Discussionsupporting
confidence: 91%
“…However, the present study was cross-sectional and could not determine the high carrier rate in the Solomon Islands. Mazzur and others 33 reported a loss of HBsAg in 20% of the HBsAg-positive subjects identified in 1974 and retested in 1977 in the Solomon Islands, although these HBsAg data were based on a reversed passive hemagglutination assay that is less sensitive than the RIA. 12 Our laboratory previously reported that the prevalence of HBV infection has remarkably decreased in children and young adults in Okinawa, a subtropical area in Japan that was endemic for HBV from 1970 to 1996 because of both the impact of vaccination and improvements in sanitary conditions, and suggested that HBV infection will be eliminated there in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…(c, d) Summarizes age dependent patterns in the force of infection from 16 different surveys, estimated by two methods (see text for details): discrete age-class (c) [42], and continuous age (d) [43]. In addition to the 13 surveys shown in (a) and (b), 3 more surveys from other highly endemic populations [35][36][37] importance of horizontal transmission is supported by t decline in the force of the results of the model which showed that the iue to common temporal observed patterns of infection could be generated by a growth. However, there is model of the horizontal spread of HBV.…”
Section: Modelling Hbv Infection Patternsmentioning
confidence: 99%
“…The [26], Zambia [27], Nairobi [28], Senegal [30], South Africa [31], Taiwan [32], four surveys from the Philippines [33] and one from Shanghai [34]. In addition to the surveys from sub-Saharan Africa and east Asia, three more studies from other highly endemic populations were included, from French Polynesia [35], Solomon Islands [36] and Venezuela [37]. A variety of serological tests were used in the surveys for detection of serological markers.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with HBV frequently remains unnoticed, and might only be noticed by seroconversion to HBsAg-positive or anti-HBc-positive results, or mild-to-moderate elevation of transaminases [7]. Several vaccine trials comparing vaccine to placebo arms have indicated that the majority of patients contracting HBV actually will have some liver enzyme elevation [8]; however, jaundice was not mentioned in these publications, suggesting significant jaundice is indeed a relatively infrequent event.…”
Section: Natural Course Of Acute Hepatitis B Virus Infectionmentioning
confidence: 99%